What can we learn from Zurich West for the Ruhr Region - From Political Stalemates, the Power of Economic Interests and Cooperative Development Planning? - Thissen, Fee (Lit, 2020)
In the context of a widening perspective in dealing with the process design of the redevelopment of wasteland, the view is directed to Zurich West. This inner-city development area in the west of the metropolitan city Zurich has undergone manifold changes through political, economic, spatial and social restructuring since 1990. The former industrial area, comprised of approx. 145 ha bare ground surface was not one coherent industrial zone, but rather contained various industrial businesses on different sites. What lessons learned from the experiences made in Zurich West can we ultimately apply to the Ruhr Region? The Zurich West experience shows how various conflicts and blockades that come about in such processes can limit or prevent the desired objectives in the following ways: (1) Impact of political conflicts on planning processes and structural changes, (2) Regional transformation as a result of economic interests, (3) Development of public districts on mainly private property by cooperation as strategic action: The experiences gained in Zurich West demonstrate that informal negotiations between private and public actors finally initiated the transformation of the former industrial area. This so-called `cooperative development planning' took place later, among actors who provided private property or investments.
Keywords: Stadtumbau; Industriegebiet; Brachflächenrecycling; Restrukturierung; Entwicklungsplanung; Planungsprozess; Kooperationsform; Stadtplanung; Privatwirtschaft; Fallbeispiel